The Influence of the Problem-Based Learning Model on the Improvement of Geography Literacy Skills - Nurdessyanah, Ade; Maryani, Enok; Sapriya, Sapriya (Journal of Innovation and Research in Primary Education, 2025)
This study investigates the effects of the Problem-Based Learning (PBL) model on improving fifth-grade students’ geographic literacy skills. The research employed a quasi-experimental method with a pre-test and post-test control group design. Participants were 60 fifth-grade students from two public elementary schools in West Java, Indonesia, selected through purposive sampling. The experimental group (n = 30) received PBL intervention, while the control group (n = 30) was taught through Discovery Learning. Data were collected using a geographic literacy test that was previously tested for validity and reliability. The intervention was implemented over nine meetings, each lasting 90 minutes. The data were analysed using normality and homogeneity tests, paired t-test, and N-Gain analysis. The results show a significant improvement in geographic literacy in the experimental class (p < 0.05), with a mean N-Gain of 72.6% (quite effective), while the control class scored 35.3% (ineffective). Furthermore, the post-test mean score of the experimental group (79.17) was significantly higher than that of the control group (68.67). The study concludes that the PBL model is more effective than Discovery Learning in enhancing geographic literacy skills of elementary school students.